A Novel Neuropredictive SAR ADC Architecture for Ultra-Low Power Applications - Spielberger, Alexander; Pfannenmüller, Christof; Spitzkopf, Lucas; Armbrecht, Wolfgang; Schrotz, Albert-Marcel; Weigel, Robert; Franchi, Norman (68th IEEE International Midwest Symposium on Circuits and Systems, 2025)
This paper proposes a new type of neuromophic analog to digital converter, the neuropredictive SAR ADC. By estimation of the next input value using a neuromorphic predictor, the conversion time of a modified SAR ADC and thus the energy consumption of the ADC can be reduced. A demonstrator designed for audio signals shows an energy saving of 41.09% compared to conventional SAR sampling. This ADC architecture is an alternative for ultra-low power application
https://cris.fau.de/converis/publicweb/Publication/342443079
Keywords: neuromorphic adc; neuropredictive SAR; SAR; ultra-low power